2005
DOI: 10.1073/pnas.0507832102
|View full text |Cite
|
Sign up to set email alerts
|

Mouse lackingCOUP-TFIIas an animal model of Bochdalek-type congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH), a life-threatening anomaly, is a major cause of pediatric mortality. Although the disease was described >350 years ago, the etiology of CDH is poorly understood. Here, we show that tissue-specific null mutants of COUP-TFII exhibit Bochdalek-type CDH, the most common form of CDH. COUP-TFII, a member of orphan nuclear receptors, is expressed in regions critical for the formation of the diaphragm during embryonic development. Ablation of COUP-TFII in the foregut mesenchyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
141
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 32 publications
7
141
0
Order By: Relevance
“…COUP-TFII (Nr2f2 -Mouse Genome Informatics), an orphan nuclear receptor, is essential for the morphogenesis of multiple organs (Takamoto et al, 2005a;Takamoto et al, 2005b;You et al, 2005a;You et al, 2005b;Kurihara et al, 2007;Petit et al, 2007;Li et al, 2009;Kim et al, 2009;Tang et al, 2010;Lin et al, 2010). In this study, we found that COUP-TFII was strongly expressed in the CGE, and we generated a conditional mutant that eliminated COUP-TFII function in the ventral telencephalon with RxCre.…”
Section: Introductionmentioning
confidence: 84%
“…COUP-TFII (Nr2f2 -Mouse Genome Informatics), an orphan nuclear receptor, is essential for the morphogenesis of multiple organs (Takamoto et al, 2005a;Takamoto et al, 2005b;You et al, 2005a;You et al, 2005b;Kurihara et al, 2007;Petit et al, 2007;Li et al, 2009;Kim et al, 2009;Tang et al, 2010;Lin et al, 2010). In this study, we found that COUP-TFII was strongly expressed in the CGE, and we generated a conditional mutant that eliminated COUP-TFII function in the ventral telencephalon with RxCre.…”
Section: Introductionmentioning
confidence: 84%
“…These findings raise the possibility that there may be diaphragm-independent causes of lung abnormalities in CDH. Indeed, lung growth and patterning defects have been observed in animal models of CDH prior to normal diaphragm closure (14)(15)(16)(17)(18)(19). However, there has been no clear in vivo demonstration as yet that PH can arise independently of the diaphragmatic defect and herniation seen in CDH.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, COUP-TFI and COUP-TFII (Nr2f1 and Nr2f2) are essential for early neural development and organogenesis (Qiu et al, 1997;Zhou et al, 1999;Pereira et al, 1999;You et al, 2005a;You et al, 2005b;Li et al, 2009;Kurihara et al, 2007;Petit et al, 2007;Takamoto et al, 2005a;Takamoto et al, 2005b). However, the physiological function of COUP-TFs in the mammalian eye has not been described.…”
Section: Introductionmentioning
confidence: 99%